Volatile compounds detected by SPME-GC-MS in fish viscera extracts with attractant activity against house fly musca domestica from chemometric FTIR fingerprints - Garwan, Rahmatia; Lioe, Hanifah Nuryani; Nurhayati, Tati; Yuliana, Nancy Dewi; Supriyono,; Kusumaningrum, Harsi Dewantari (Penerbit Universiti Kebangsaan Malaysia, 2023)
Fish viscera has been locally applied as fly attractant in North Moluccas. The objective of this study was to evaluate the efficacy of attractant from fish viscera extracts and to determine the indispensable active extracts with chemometric FTIR fingerprints, as well as to characterize volatile compounds of the extracts. Attractant activity against house fly Musca domesctica and FTIR spectra were analyzed for the ethanol, acetone and hexane extracts of stomach, intestines, liver, and combination of the viscera from skipjack tuna stored for 1-2 days at room temperature. SPME-GC-MS analysis was applied for active extracts to determine volatile compounds. OPLS analysis result showed that FTIR spectra were correlated with the attractant activity (R2 0.974 and Q2 0.89), and compounds with functional groups S-H, N-H, O-H, and C-O have the strong correlation. Ethanol and acetone extracts of mixed viscera from 2 days storage are the active extracts. The volatile compounds in the extract through the SPME-GC-MS analysis belong to ketone, amine, phenol, heterocyclic, aromatic aldehyde, fatty acid, fatty acid ester and sulfur compounds are reported.